Peran Badan Wakaf Indonesia (BWI) Dalam Mengembangkan Prospek Wakaf Uang Di Indonesia - Muhammad Aziz (Universitas Islam Lamongan, 2017)
Since established in 2007, Indonesian waqf Board (BWI) which is based upon the mandate of Law No. 41 of 2004 on waqf has had a significant role in the dynamics of waqf management in Indonesia. However, a significant role still has not been completed. The problems of waqf in Indonesia still exist, especially with regard to waqf money (cash waqf). The study is to answer question; how is the role of Indonesian Waqf Board and any effort which should be done, so that the potential of existing cash waqf in Indonesia can grow and develop. From this research, it can be concluded that the role of Indonesian Waqf Board in developing prospects in Indonesia is less maximal. Waqf money can not be mapped on the following things; First, professional nazhir coaching, particularly against individuals or legal entities who are given authority and responsibility as nazhir of money waqf. To improve the quality of human nazhir resources, it can be needed policies that are tentative, or even a steady, so that taste and look for nazhir usefulness. Second, involving strategic business partners engaged in financial services (especially sharia-based), such as banks, cooperatives, Baitul Maal wal Tamwil (BMT) and the like, in the process of promotion and dissemination of money waqf that is being developed by BWI. All that prospects and public confidence in the waqf money at BWI can flourish. Keywords: Cash Waqf, BWI, Nazhir, Law of the RI Number 41 of 2004 on Waqf